2003
DOI: 10.1021/jp027432b
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron SAXS Study of the Mechanisms of Aggregation of Sulfate Zirconia Sols

Abstract: This is a systematic investigation, using in situ synchrotron small-angle X-ray scattering, of the mechanisms of aggregation of sulfate zirconia sols under different preparation conditions. We have studied the effects of the variations of acid, water, and sulfate contents on the process of aggregate growth. These effects were investigated using open and sealed sample cells. It was observed that two clearly different mechanisms govern the aggregation at the beginning and at advanced stages of the process. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 43 publications
6
22
1
Order By: Relevance
“…Both groups found that cylinder shaped particles of constant cross-sectional radius formed in early stages of sol development. An analogous polydisperse cylinder model was used to analyze data [60], yielding comparable results as I obtained here. The measured radius of the cylinder crosssection equaled 0.46 nm.…”
Section: Interpretation Of Datasupporting
confidence: 54%
See 3 more Smart Citations
“…Both groups found that cylinder shaped particles of constant cross-sectional radius formed in early stages of sol development. An analogous polydisperse cylinder model was used to analyze data [60], yielding comparable results as I obtained here. The measured radius of the cylinder crosssection equaled 0.46 nm.…”
Section: Interpretation Of Datasupporting
confidence: 54%
“…Thus, only the central Zr-based framework contributes to scattering contrast. This may explain why the cross-sectional radius observed by me is lower than in studies where zirconia chloride, nitrate, and sulphate salts were synthesized [59,60]. In the zirconia sol L w increased only slightly from 1.79 to 1.85 nm.…”
Section: Interpretation Of Datamentioning
confidence: 62%
See 2 more Smart Citations
“…Zirconium salt solutions have a number of industrial uses [59,60] and their chemistry has been studied extensively [61][62][63][64][65][66][67][68][69][70][71][72][73]. In general, zirconium(IV) cations have a strong tendency to hydrolyze in aqueous medium, i.e.…”
Section: Formation Of Primary Solidmentioning
confidence: 99%